Characterization of domestic waste based on BOD, COD and TSS parameters - Ro'in, Nur Fadillatur; Dahalan, Farah Aini (Environmental and Toxicology Management, 2024)
The negative impact of domestic waste water discharge is a decrease in water quality in the receiving water body due to reduced dissolved oxygen, which can result in the death of aquatic organisms. Increased concentrations of BOD (Biological Oxygen Demand), COD (Chemical Oxygen Demand), and TSS (Total Suspended Solid) in domestic waste can have a negative impact on the environment through a series of interrelated processes such as triggering the phenomenon of eutrophication, where algae growth becomes uncontrollable and disrupts the balance of aquatic ecosystems. When BOD and COD levels increase, it indicates an excessive accumulation of organic matter and pollutants in the water, resulting in a decrease in dissolved oxygen due to oxygen consumption by microorganisms that decompose the organic matter. Several previous studies related to the quality characteristics of domestic wastewater were analyzed to determine its quality in the parameters of BOD, COD, and TSS. As a result, most of the domestic wastewater quality has a quality that exceeds the required quality standards. The average quality of domestic wastewater in the parameters of BOD, COD, and TSS is 541.9 mg/L, 1318.4 mg/L, and 1986.8 mg/L, respectively. The BOD and COD ratio shows 0.4, domestic waste must go through the seeds to be decomposed.